Guía de uso y aplicación de marketing digital a través de marketing de contenidos y social CRM para la gestión de empresas de servicio público. Caso: empresa pública metropolitana de Agua Potable y Saneamiento (EPMAAPS) - Michelena Ruiz, Esteban Santiago (2014)
The irruption of new technologies has transformed the communications and how people and organizations interact. With the Internet the access and production of information were democratized. Today any user with an Internet connection can create his own media. This technology boom brings an information overloaded era. In fact, each second means 2.8 million emails and 1.633 tweets. Every minute, 694.455 queries are typed on Google and 600 videos are uploaded on YouTube. Also, 320 new accounts are registered at Twitter. Finally, 780.000 apps are downloaded and 4.200 new domains are bought. This situation develops an infoxication scene and a new question. ¿How people and organizations could advantage the Internet and dialogue with their audiences? Digital Marketing, Content Marketing and Social CRM become into three value tools for the enterprises to connect with their audiences and construct long time relationships. In this way, with the variables mentioned an enterprise will know how to use the Internet and take advantage from their competitors.